Evolution of inflorescence branch modifications in cereal crops. (February 2022) - Koppolu, Ravi; Chen, Shulin; Schnurbusch, Thorsten
Abstract: Grasses are ubiquitous in our daily lives, with gramineous cereal crops such as maize, rice, and wheat constituting a large proportion of our daily staple food intake. Evolutionary forces, especially over the past ∼20 million years, have shaped grass adaptability, inflorescence architecture, and reproductive success. Here, we provide basic information on grass evolution and inflorescence structures mainly related to two inflorescence types: branched panicle- and spike-type inflorescences, the latter of which has highly modified branching. We summarize and compare known genetic pathways underlying each infloresecence type and discuss how the maize RAMOSA, rice ABERRANT PANICLE ORGANIZATION, and Triticeae COMPOSITUM pathways are regulated. Our analyses might lay the foundation for understanding species-specific gene regulatory networks that could result in improved sink capacities.